Diversity and distribution of symbiodinium associated with seven common coral species in the Chagos Archipelago, central Indian Ocean. - Sung-Yin Yang; Shashank Keshavmurthy; David Obura; Charles R C Sheppard; Shakil Visram; Chaolun Allen Chen (PLoS ONE, 2012)
The Chagos Archipelago designated as a no-take marine protected area in 2010, lying about 500 km south of the Maldives in the Indian Ocean, has a high conservation priority, particularly because of its fast recovery from the ocean-wide massive coral mortality following the 1998 coral bleaching event. The aims of this study were to examine Symbiodinium diversity and distribution associated with scleractinian corals in five atolls of the Chagos Archipelago, spread over 10,000 km(2). Symbiodinium clade diversity in 262 samples of seven common coral species, Acropora muricata, Isopora palifera, Pocillopora damicornis, P. verrucosa, P. eydouxi, Seriatopora hystrix, and Stylophora pistillata were determined using PCR-SSCP of the ribosomal internal transcribed spacer 1 (ITS1), PCR-DDGE of ITS2, and phylogenetic analyses. The results indicated that Symbiodinium in clade C were the dominant symbiont group in the seven coral species. Our analysis revealed types of Symbiodinium clade C specific to coral species. Types C1 and C3 (with C3z and C3i variants) were dominant in Acroporidae and C1 and C1c were the dominant types in Pocilloporidae. We also found 2 novel ITS2 types in S. hystrix and 1 novel ITS2 type of Symbiodinium in A. muricata. Some colonies of A. muricata and I. palifera were also associated with Symbiodinium A1. These results suggest that corals in the Chagos Archipelago host different assemblages of Symbiodinium types then their conspecifics from other locations in the Indian Ocean; and that future research will show whether these patterns in Symbiodinium genotypes may be due to local adaptation to specific conditions in the Chagos.